Dakwah Smart: Proses Dakwah sesuai dengan Aspek Psikologis Mad’u - Enjang AS (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
Da’wah has psikological dimension.In aplicate, smart and not smart of da’wah is so determinated by da’i attention to psychological aspecs of mad’u such comprehension, feeling, attitude, motif and behavior. Da’wah become smart, in really, constitue da’i maximum effort in controlling and develop psychological aspecs of mad’u that da’wah become effective.